Placing research within Strathmore university corporate strategy - (:unkn) unknown (My University, 2015)
The aim of this paper is to answer the question, “how can strategic planning help new universities re-define the meaning of scholarship?” The old Traditional universities (older than 100 years) have perfected their existence as sources of knowledge through basic research and publications. However, most of the newer universities, so called “teaching universities”, have on the other hand concentrated on scholarly teaching rather than research. There has also been a growing demand for a third type of recognition; the recognition for service that will transfer knowledge from universities to the industry or society. The paper highlights how strategic planning and implementation has helped Strathmore University to address these conflicting types of scholarship.
Paper Presented at the Strathmore Research Week Workshop; 27th – 31st July 2009
The aim of this paper is to answer the question, “how can strategic planning help new universities re-define the meaning of scholarship?” The old Traditional universities (older than 100 years) have perfected their existence as sources of knowledge through basic research and publications. However, most of the newer universities, so called “teaching universities”, have on the other hand concentrated on scholarly teaching rather than research. There has also been a growing demand for a third type of recognition; the recognition for service that will transfer knowledge from universities to the industry or society. The paper highlights how strategic planning and implementation has helped Strathmore University to address these conflicting types of scholarship.
Keywords: Corporate strategy